2020
DOI: 10.1155/2020/5759083
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trials of Tianma Gouteng Decoction Combined with Nifedipine in the Treatment of Primary Hypertension: A Systematic Review and Meta‐Analysis

Abstract: Background. Hypertension is a primary risk factor for cardiovascular disease (CVD). Tianma Gouteng decoction (TGD), originating from Zabingzhengzhixinyi, has been used for thousands of years in China to treat hypertension, giddiness, and migraine. This updated meta-analysis aimed at assessing the efficacy and safety of TGD combined with nifedipine in the treatment of primary hypertension. Methods. Related research published prior to September 1, 2019, was found in electronic databases without language limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Past reports of combining antihypertensives and traditional herbal medicines to treat hypertension exist [2, 8]. Almost all these studies considered traditional herbal medicine as a modern antihypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…Past reports of combining antihypertensives and traditional herbal medicines to treat hypertension exist [2, 8]. Almost all these studies considered traditional herbal medicine as a modern antihypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium channel blockers, such as Nif, have frequently been used as effective drugs in patients with hypertension [ 89 ]. Corresponding to the worldwide increase in patients with hypertension, Nif is now more frequently used in clinical settings [ 69 ].…”
Section: Drug-induced Gingival Overgrowthmentioning
confidence: 99%
“…Accumulating studies have revealed that IR is closely related to hypertension (3)(4)(5)(6), increased blood pressure can increase IR, and long-term IR can increase blood sugar to form a vicious circle, so hypertension and IR interact with each other and promote each other (7). Additionally, recent studies (8) found that oxidative stress damage is a vital pathophysiological mechanism leading to hypertension and IR.…”
Section: Introductionmentioning
confidence: 99%